Homing blogs as ambivalent spaces for feminine agency. Issue 5 (3rd September 2018) - Jäntti, Saara; Saresma, Tuija; Leppänen, Sirpa; Järvinen, Suvi; Varis, Piia
Abstract: This article discusses a form of lifestyle blogging where women blog about their homes and everyday lives. In these homing blogs, self-representations are characteristically spatially demarcated within the private sphere of the home. As these repeated representations of women in their homes take place in the public space of the internet, homing blogs work towards naturalizing the home as a women's sphere. Written and commented on mostly by other women, homing blogs represent a feminine form of self-expression and communication that functions as a discursive expression of ongoing social, economic, and cultural changes in affluent Western societies. In this article, Finnish versions of these homing blogs are analysed in the cultural and political context of contemporary Finland, and discussed as a form of intimate publics that reverses the gender politics of other historical, semi-public spaces for the exercise of women's agency, such as the salon.